2014
DOI: 10.4236/ojml.2014.41001
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Retroactive Transfer (CRT) of Language Skills among Trilingual Arabic-Hebrew and English Learners

Abstract: This study examined whether helping poor readers improve their reading and writing language skills in English as a third language/foreign language (L3/FL) would also bring about an improvement in those same skills in Arabic (L1) and Hebrew (L2). Transferring linguistic skills from L3/FL to both L1 and L2 is termed "Cognitive Retroactive Transfer" (CRT). A battery of tests, administered to the experiment and control groups, assessed orthographic knowledge, phonological awareness, morphological awareness, syntac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 95 publications
5
15
0
3
Order By: Relevance
“…In other words the Greek orthographic skills did not improve since according to our results, the English orthographic experiences were not transferred to Greek (L1). This finding seems to be consistent with previous studies that did not find orthographic cross language transfer (Abu-Rabia & Bluestein-Danon, 2012;Abu-Rabia & Shakkour, 2014;Abu-Rabia, Shakkour, & Siegel, 2013;Wang, Park, & Lee, 2006;Wang, Perfetti, & Liu, 2005). Abu-Rabia & Siegel, (2002) claim that orthographic skills are language specific and therefore every language has unique orthographic rules.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In other words the Greek orthographic skills did not improve since according to our results, the English orthographic experiences were not transferred to Greek (L1). This finding seems to be consistent with previous studies that did not find orthographic cross language transfer (Abu-Rabia & Bluestein-Danon, 2012;Abu-Rabia & Shakkour, 2014;Abu-Rabia, Shakkour, & Siegel, 2013;Wang, Park, & Lee, 2006;Wang, Perfetti, & Liu, 2005). Abu-Rabia & Siegel, (2002) claim that orthographic skills are language specific and therefore every language has unique orthographic rules.…”
Section: Discussionsupporting
confidence: 92%
“…However, the spelling results of the experimental group revealed a different pattern; regarding the third research question, the L2 orthographic results of the experimental group improved as a result of the intervention. This finding is supported by other studies that also found an improvement in orthography after an intervention in L2 among struggling readers (Abu-Rabia & Bluestein-Danon, 2012;Abu-Rabia & Shakkour, 2014;Abu-Rabia, Shakkour, & Siegel, 2013).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Those research findings are based on the hypothesis that there is a close relation between the students' skills in their first language and those in their second/foreign language (Sparks, 2012). At the same time, researchers orientate themselves towards the study of crosslanguage skills transfer (Abu-Rabia & Shakkour, 2014) and the role of the characteristics of each language system (Seymour, Aro & Erskine, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In the 1960s and 1970s, the influence of the rise of cognitive science on linguistics and psychology, especially the proposition of Chomsky's linguistic theory, shifted the perspective of language transfer from the comparison of language morphology to the study of the general development of English acquisition. Researchers pay attention to the universal development law in the process of English acquisition, and discuss the generation process of "interlanguage" in language acquisition instead of the hypothesis theory of contrastive analysis (Aburabia and Shakkour, 2014). Therefore, language transfer is no longer a common interpretation of language misuse in the process of language acquisition, but interlanguage hypothesis theory.…”
Section: Introductionmentioning
confidence: 99%